A fragilidade do ambiente organizacional do arranjo produtivo local calçadista de Franca-SP - Tizziotti, Catarine Palmieri Pitangui (2013)
If a productive clusters can maintain its existence in time, it is interesting to note what their specific attributes, and the nature of their collective efficiency. From this perspective, this work aims to show organizational relationships that occur within the Local Productive Arrangement (APL) from Franca and thus observe what effects the actions of these actors in APL. To this was done through an exploratory survey of secondary data, and semistructured interviews with representatives of professional associations and local government.